Pengaruh Edukasi Menggunakan Media Booklet Terhadap Pengetahuan Ibu Primigravida Mengenai Ketubah Pecah Dini di Wilayah Kerja Puskesmas Mubune Kecamatan Likupang Barat - Farah Aprilia Deswinta Hasyim (Lembaga Pengembangan Kinerja Dosen, 2025)
Premature rupture of membranes is the breaking of the membranes before there are signs of labour. The incidence of premature rupture of membranes occurs in 10-12% of all pregnancies. In a term pregnancy, the incidence is 6-19%, while in preterm pregnancy it is 2-5%. The purpose of this study was to find out the effect of education using booklet media on the knowledge of primigravida mothers regarding premature rupture of membranes in the working area of the Mubune Health Centre, West Likupang District. The research was conducted using the One Group Pre-test - Post-test Design research method. The sample of respondents was 24 respondents using purposive sampling technique. Data collection using questionnaires and observations. Furthermore, the data that has been collected was processed by running the SPSS version 26 program to be analysed with the Wilcoxon Signed Rank Test statistical test. The results showed that most of the primigravida mothers before being given education had poor knowledge. After being given education through booklet media, most respondents had good knowledge. The results of the Wilcoxon Signed Rank Test test obtained the value of Asymp. Sig (2-tailed) is smaller than the alpha value (α) 0.05.